Kesetaraan gender dalam pendidikan: pendekatan humanisme untuk generasi masa depan - Ariyani, Nafiska (Maliki Interdisciplinary Journal, 2025)
Gender equality in education is a crucial foundation for creating an inclusive and just society. This article explores education as a strategic means to reduce gender disparities through a humanistic approach. By embracing humanistic values, education can dismantle gender stereotypes and establish a more inclusive space for all individuals, both men and women.This approach involves designing gender-responsive curricula, implementing supportive government policies, and fostering collaboration with various stakeholders. Challenges such as social norms that confine women to domestic roles and unequal access in remote areas must be addressed through empowerment programs and technological advancements. Equitable education not only broadens access but also provides opportunities for women to thrive equally, particularly in fields traditionally dominated by men. Through the implementation of humanistic curricula and proactive policies, future generations are expected to embrace the values of diversity and social justice. This article emphasizes that gender equality in education is not merely an aspiration but an essential need for building a better society.